Homoseksualiteit en fascisme : scholingsmap - Vermeulen, Mary; Odijk, Michiel; Verschuren, Peter; Schuyf, Judith; Oosterhuis, Harry; Koenders, Pieter (Utrecht: AFKU; COC, 1984)
"Fonds Suzan Daniel (FSD)"